KEABSAHAN PEMIMPIN GANDA DALAM KEPENGURUSAN KOPERASI MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2012 TENTANG PERKOPERASIAN - Hamonangan, Jeffryanto; -, Marwanto; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013)
The article is about much validity in the management of the cooperative inaccordance with the law number 17 of 2012 about cooperation. With the aim of facing thedouble role of managers in the management of Co-operatives and the adoption of thefollowing managers before ending the first manager of the department time and gain anunderstanding of the role of the Law number 17 of 2012 on the management of cooperationas a protective container Cooperative. Used in writing this essay is writing method normativelegal scrutiny. That occupy multiple departments in a legal form of business entity is notgiven, as it will affect the performance and progress of a society according to State Gazetteof the Republic of Indonesia Year 2012 Number 212.
Keywords: Double manager, Cooperative, Incumbency